2021
DOI: 10.1007/s12525-021-00458-3
|View full text |Cite
|
Sign up to set email alerts
|

Understanding continued smartwatch usage: the role of emotional as well as health and fitness factors

Abstract: Smartwatches are the most popular wearable device and increasingly subject to empirical research. In recent years, the focus has shifted from revealing determinants of smartwatch adoption to understanding factors that cause long-term usage. Despite their importance for personal fitness, health monitoring, and for achieving health and fitness goals, extant research on the continuous use intention of smartwatches mostly disregards health and fitness factors. Grounding on self-determination theory, this study add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 72 publications
(119 reference statements)
0
20
0
1
Order By: Relevance
“…This behavior includes users receiving tailored analyses of their health status and physical activity, so health-seeking users are increasingly self-measuring. We therefore hypothesized that high self-quantifiers will become more attached to the technological devices on their wrists ( Siepmann and Kowalczuk, in press ). Individuals with higher anxiety about COVID-19 will have a negative affective reaction toward technology use due to their anxious feelings, and their anxiety will weaken their continuance use intention ( Venkatesh, 2000 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This behavior includes users receiving tailored analyses of their health status and physical activity, so health-seeking users are increasingly self-measuring. We therefore hypothesized that high self-quantifiers will become more attached to the technological devices on their wrists ( Siepmann and Kowalczuk, in press ). Individuals with higher anxiety about COVID-19 will have a negative affective reaction toward technology use due to their anxious feelings, and their anxiety will weaken their continuance use intention ( Venkatesh, 2000 ).…”
Section: Methodsmentioning
confidence: 99%
“…By wearing a smartwatch continuously, users can benefit from the available features as it encourages them to lead healthier lifestyles ( Siepmann and Kowalczuk, in press ). With this concept in mind, the present study adapted the Product Continuance Intention Scale designed by Hong et al (2017) with six items to measure the participants’ intention to continue using the smartwatch for guided respiration practice.…”
Section: Methodsmentioning
confidence: 99%
“…Considering scholars in the field of information systems and marketing have pointed out that loyalty is a complex psychological construct that has multiple specific behavioral manifestations [39,40], such as continuation [8,41,42], recommendation [27,43,44], and cross-buy [45][46][47], this study operates with user loyalty as a second-order formative construct involving the above three sub-behaviors. Specifically, continuation means the extent to which users are willing to continue using the smart health devices in the future; recommendation refers to the extent to which users are willing to recommend the smart health devices to others; and cross-buy captures users' additional buying behavior (i.e., products and services) from the existing smart health devices provider that they use.…”
Section: Research On Users' Loyalty To Smart Health Devicesmentioning
confidence: 99%
“…According to the expectation confirmation theory, satisfaction is a direct determinant of loyalty, and it thus has been regarded as a good mediating variable in previous smart health device studies [42,71,72]. For example, Bölen [72] found that perceived usefulness and aesthetics were direct antecedents of satisfaction, which positively impacted users' continuance intention.…”
Section: The Mediating Role Of Satisfactionmentioning
confidence: 99%
“…However, the attachment of multiple sensors negates the wearable sensor's advantages of portability, comfort, and ease of acceptance by users in real-world environments [11]. The smartwatch, which has only a single IMU sensor, is the most popular wearable device for the assessment of physical activity via energy expenditure and steps during daily activities [10,12]. However, because the smartwatch relies on the degrees of upper limb motion [6], the data are subject to motion artefacts and do not measure the trunk motion during squat and lunge exercises; notably, trunk kinematic data in the sagittal or frontal plane have been used for effective training (e.g., to contract hip and knee muscles) and screening (e.g., to identify people developing knee pain during lunge and squat exercises) [11,13].…”
Section: Introductionmentioning
confidence: 99%